Performance analysis of gray code number system in image security - Akinbowale Nathaniel Babatunde; Ebunayo Rachael Jimoh; Oladipupo Oshodi; Olujuwon Ayoseyi Alabi (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2019)
The encryption of digital images has become essential since it is vulnerable to interception while being transmitted or stored. A new image encryption algorithm to address the security challenges of traditional image encryption algorithms is presented in this research. The proposed scheme transforms the pixel information of an original image by taking into consideration the pixel location such that two neighboring pixels are processed via two separate algorithms. The proposed scheme utilized the Gray code number system. The experimental results and comparison shows the encrypted images were different from the original images. Also, pixel histogram revealed that the distribution of the plain images and their decrypted images have the same pixel histogram distributions, which means that there is a high correlation between the original images and decrypted images. The scheme also offers strong resistance to statistical attacks.